Experimntal study on sludge solidification in a landfill site in Shenzhen. Issue 1 (January 2021) - Gan, Yu; Su, Shengxi; Guo, Jing; Huang, Jie; Ding, Jihui
Abstract: As urban land use is relatively tight, the rational use of sludge landfills has become a problem that must be solved. Because the sludge has the characteristics of high water content, poor permeability, strong flocculation, high combined water content, and high organic matter content, the traditional vacuum preloading method, stacking preloading method and other curing methods are too inefficient and can not meet engineering requirements. In this paper, an indoor electroosmosis drainage consolidation test was designed for sludge in a sludge landfill area in Shenzhen. The test results show that the reasonable drainage method, stacking method and shortening the electrode spacing increase the strength of solidified sludge by 1.1 times, 1.6 times and 2.8 times. The water content is reduced by 19.8%, 25.5% and 55.6%.The drainage rate is linear with the current.